Embedded multitasking - Curtis, Keith, 1961- (Embedded technology series.)
In an embedded system, firmware is the software that directly interfaces with the microcontroller, controlling the system?s function. The major forces driving the embedded firmware development process today are reduced development times, increased complexity, and the need to handle multiple tasks simultaneously. These forces translate into strenuous design requirements for embedded engineers and programmers. Many low-level embedded microcontroller designs have insufficient memory and/or architectural limitations that make the use of a real-time operating system impractical. The techniques pres.